Methods of Criminological Research, 1st edition - Jupp, Victor R (Routledge, 2020)
Examining the different ways in which data can be collected and analyzed for research on crime and criminal justice, this book deals with social surveys, experimental methods, official statistics, observation and detailed interviews. This practical text includes sections on: